Application of comprehensive u nit-based safety program model in the inter-hospital transfer of patients with critical diseases: a retrospective controlled study - Yimei Gu; Lina Liang; Liuna Ge; Ling Jiang; Xiaole Hu; Jing Xu; Yu Cao; Xiaoting Feng (BMC, 2021)
Abstract Background To explore the effect of applying a comprehensive unit-based safety program (CUSP) in the intrahospital transfer of patients with critical diseases. Methods A total of 426 critically ill patients in the first affiliated Hospital of Anhui Medical University from August 2018 to February 2019 were divided into two groups according to the time of admission. Overall, 202 patients in the control group were treated with the routine transfer method, and 224 patients in the observational group were treated with the transfer method based on the CUSP model. The safety culture assessment data of medical staff, the occurrence rate of adverse events and related causes, the time of transfer, and the satisfaction of patients' relatives to the transfer process were compared before and after implementation of the transfer model between the two groups. Results Before and after the implementation of the CUSP mode transfer program, there were significant differences in the scores of all dimensions of the safety culture assessment of medical staff (P < 0.05), and the occurrence rate of adverse events and the causes in the observational group were significantly lower than those in the control group (disease-related, staff-related, equipment-related, environment-related) (P < 0.05). The transfer time for Computed Tomography (CT), Magnetic Resonance Imaging (MRI), operating room, and the interventional room was significantly shorter in the observational group than that in the control group (P < 0.05), while the satisfaction of relatives to the transfer process was significantly higher than those in the control group (P < 0.05). Conclusion The implementation of CUSP model for the intrahospital transfer of critically ill patients can significantly shorten the in-hospital transfer time, improve the attitude of medical staff towards safety, reduce the occurrence rate of adverse events, and improve the satisfaction of patients' relatives to the transfer process.